Electric and Acoustic Stimulation in Cochlear Implant Recipients with Hearing Preservation - Welch, Christopher; Dillon, Margaret T.; Pillsbury, Harold C. (Seminars in Hearing, 2018)
Hearing loss affects 30 million people in the United States, and a subset of these patients have normal low-frequency hearing and ski-sloped high-frequency hearing loss. For these patients, hearing aids alone may not provide adequate benefit. Cochlear implantation alone has been utilized to improve speech perception. The addition of high-frequency electric hearing to low-frequency acoustic hearing in these patients is beneficial. Technical improvements have allowed preservation of low-frequency hearing in cochlear implant recipients, allowing for electric and acoustic stimulation in the same ear with significant improvements in speech perception, sound localization, music appreciation, and quality of life.
Keywords: cochlear implantation; electric and acoustic stimulation; hearing loss; hearing preservation cochlear implantation